IMPLEMENTASI PEMBERIAN BANTUAN HUKUM DALAM PROSES PENYIDIKAN DI KEPOLISIAN RESORT POLEWALI MANDAR - Salam, Abdul (Siddiq Institute, 2022)
The purpose of this study to determine the fulfillment of the right to legal assistance for the suspect/defendant at the police station Polman Polewali Mandar and to identify constraints faced by officers in fulfilling the right to legal assistance for the suspect / defendant at the police station Polman Polewali Mandar. This research was conducted at the police station to find out Polman Samples were two investigators from the Police Polman Polman, a lawyer from the Legal Aid Institute Polman as many as two people, accused/suspect criminal cases as much as 2 people. Data collection techniques used were observation, interviews and documents. Data analysis techniques used are the stages of data reduction, data presentation stage. And the stage conclusion. Research results obtained in the examination of legal counsel investigation still suspected of being people who are disrupting the examination. Has not been granted, and laid foundation of equality and the position of attorney-investigator is a problem in the provision of legal aid.